PENGARUH KONSELING KELOMPOK BEHAVIOR CONTRACT TERHADAP PENINGKATAN KEDISIPLINAN SISWA - Askia Widiyanti; Nofi Nur Yuhenita; Sugiyadi Sugiyadi (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2024)
This study aims to examine the effect of group counseling with behavior contract in improving student discipline at school. This research was conducted on students of Class XII MIPA 2 SMA Negeri 2 Kota Magelang for the 2023/2024 academic year. The type of research used in this study is pre-experiment with the One Group Pretest Posttest Design model. The research subjects were selected by quota sampling. The sample in this study was 7 students as an experimental group. The data collection method was carried out using student discipline questionnaires. The data analysis method uses 26. For Windows. Shapiro Wilk's normality test on the results of the questionnaire showed normal. Data analysis is Paired sample T Test. The results of this study show that group counseling behavior contract has an effect on improving the discipline of Class XII MIPA 2 students at SMA Negeri 2 Kota Magelang. This is evidenced from the results of the analysis of the Paired Sample T Test test with significant values of 0.00 < 0.05. The results of this study concluded that group counseling behavior contract have an effect on improving discipline in Class XII MIPA 2 SMA Negeri 2 Kota Magelang students for the 2023/2024 academic year.